Analysis of relationship between hammer head velocity and radius of curvature - Fujii, N.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
In many research papers, the relationship between the hammer head velocity and the radius of curvature of hammer was discussed. The purpose of this study was to re-examine the relationship between the hammer head velocity and change in the radius of curvature with the 2-D computer simulation.